A Dual-Factor Releasing Hydrogel for Rotator Cuff Injury Repair - Teng, Chong; Fang, Yifei; Zhu, Huangrong; Huang, Leyi; Jin, Yanglei; Ye, Zhaoming (Frontiers in Materials, 2021)
Rotator cuff injury causes pain in the shoulder and is a challenge to be repaired even after surgical reconstruction. Here, we developed a dual-factor releasing hydrogel based on sulfhydrylated chitosan to deliver KGN and FGF-2 to the injured area to enable fast healing of the tendon–bone interface, which is essential for the repair of rotator cuff injury. We found that the two factors could be easily loaded into the hydrogel, which could in turn continuously release the factors in physiological conditions. The hydrogel was found to be a porous structure through a scanning electron microscope (SEM). The micropores in the hydrogel structure enable the loading and releasing of these molecules. This study showed that KGN and FGF-2 could play a synergistic effect by recruiting and promoting stem cell proliferation and chondrogenesis, thus accelerating the healing of the tendon–bone interface. An in vivo study based on a rabbit rotator cuff injury model demonstrated that the dual-factor releasing hydrogel possesses superior repair capacity than a single-factor releasing hydrogel and the untreated groups. In conclusion, the KGN and FGF-2 dual-factor releasing hydrogel could be a promising biomaterial for the regeneration of the tendon–bone interface and rotator cuff injury repair.